Risk aversion and sustainable maize production in Nigeria: some challenges and prospects for agricultural and economic development - Manyong, Victor M.; Olarinde, L. (2007)
This paper determines the degree or extent of farmer’s risk aversion that affects sustainable maize production in Northern Nigeria. Using a ridge regression analysis, a measure of risk aversion was derived for each individual farmer in a model of safety-first behaviour from a cross-sectional survey of 350 maize producers in northern Nigeria. The distribution of the degree of risk aversion shows a high skewness towards the risk averters (high risk farmers) and centered around 1.20, and standard deviation of 0.37. This distribution is then explained by a set of specific variables that characterize the farmers’ behaviour in the study area using a Tobit model. Susceptibility to risk was found to be highly premised on the socioeconomic factors (e.g. age of household head), farm specific variables (e.g. proportion of income from maize) and farmers’ attitudinal factors against risk (e.g. safety first level of probability of sale). These findings can be used to construct a framework of development programs for peasant farmers, which provide some challenging prospects.